Understanding the Challenges Experienced by COPD Patients: A Qualitative Study - Özlem Oruç; Saime Erol; Zahide Aksoy (Halk Sağlığı Hemşireliği Dergisi)
Objective: The aim of this study is to investigate the difficulties experienced by COPD patients, understand their needs, and provide a reference for the content of COPD patient empowerment programs.Method: In this study using phenomenological design, semi-structured individual in-depth interviews were conducted with 11 COPD patients using purposive sampling between May 2023 and July 2023. The transcribed interviews were transferred to the MAXQDA program for analysis. Thematic analysis was used to code the data and determine themes. The Consolidated Criteria for Reporting Qualitative Research (COREQ) checklist was used as a guide to ensure the quality of the study.Results: As a result of the analysis, five themes emerged regarding the challenges experienced in COPD: Perception of disease, difficulty in disease management, losses in lifestyle, emotional burden of the disease, need for information.Conclusions: It is thought that the interventions to be implemented to strengthen COPD patients can increase their effectiveness by creating them within the scope of the themes obtained in this study.